Public administrative science in Germany: problems and prospects of a composite discipline - Benz, Arthur (2005)
German administrative science is composed of different disciplines which combine to form a multi-rather than an interdisciplinary science. Its roots can be traced back to the integrated policy-science (Policey-Wissenschaft) of the eighteenth century, which went through a process of differentiation during the nineteenth century. In German universities today, teaching and research is divided into different departments, a main problem being the disproportionate nature of this multidisciplinary structure. In German administrative science, a legalistic approach still predominates, although, in the 1960s and 1970s, political scientists played an important role in empirical research and theoretical discussions. Looking ahead, however, there is now an excellent chance that with the rise of the governance approach this asymmetric multidisciplinarity can be turned into a more balanced administrative science, even if it will remain a composite discipline. - Reproduced.
Keywords: Public administration - Germany; Public administration